Small bowel adenocarcinoma: Results from a nationwide prospective ARCAD‐NADEGE cohort study of 347 patients. Issue 4 (22nd January 2020) - Aparicio, Thomas; Henriques, Julie; Manfredi, Sylvain; Tougeron, David; Bouché, Olivier; Pezet, Denis; Piessen, Guillaume; Coriat, Romain; Zaanan, Aziz; Legoux, Jean‐Louis; Terrebone, Eric; Pocard, Marc; et al.
Abstract : Small bowel adenocarcinoma (SBA) is a rare tumour. We conducted a prospective cohort to describe the prevalence, survival and prognostic factors in unselected SBA patients. The study enrolled patients with all stages of newly diagnosed or recurrent SBA at 74 French centres between January 2009 and December 2012. In total, 347 patients were analysed; the median age was 63 years (range 23–90). The primary tumour was in the duodenum (60.6%), jejunum (20.7%) and ileum (18.7%). The prevalence of predisposing disease was 8.7%, 6.9%, 1.7%, 1.7% and 0.6% for Crohn disease, Lynch syndrome, familial adenomatous polyposis, celiac disease and Peutz‐Jeghers syndrome, respectively. At diagnosis, 58.9%, 5.5% and 35.6% of patients had localised and resectable, locally advanced unresectable and metastatic disease, respectively. Crohn disease was significantly associated with younger age, poor differentiation and ileum location, whereas Lynch syndrome with younger age, poor differentiation, early stage and duodenum location. Adjuvant chemotherapy (oxaliplatin‐based in 89.9%) was performed in 61.5% of patients with locally resected tumours. With a 54‐months median follow‐up, the 5‐year overall survival (OS) was 87.9%, 78.2% and 55.5% in Stages I, II and III, respectively. The median OS of patients with Stage IV was 12.7 months. In patients with resected tumours, poor differentiation ( p = 0.047) and T4 stage ( p = 0.001) were associated with a higher risk of death. In conclusion, our study showed that the prognosis of advanced SBA remains poor. Tumour characteristics differed according to predisposing disease. In SBA‐resected tumours, the prognostic factors for OS were grade and T stage. Abstract : What's new? Small bowel adenocarcinoma is a rare disease but incidences are increasing in Europe and the US because of increases in duodenal cancers. This study from France found that Crohn's disease and Lynch syndrome, a genetic condition associated with colorectal cancers, combined with younger age and poor differentiation predisposed for the disease. The authors also linked poor differentiation and advanced tumor staging with short overall survival in patients with locally resected tumors, underscoring that the prognosis for advanced adenocarcinomas remains poor.